Demystifying the Religionisation of Commercial Begging in Northern Nigeria: The Revival of Philanthropy among Muslims - Rabiu, Aliyu Alhaji; Dahiru Idriss, Ibrahim; Rabiu , Sani (IIUM Journal of Religion and Civilisational Studies, 2025)
This paper explores the concept of ṣadaqah (voluntary charity) in Islam, emphasising its role in encouraging Muslims to fulfil their social responsibility by providing financial assistance to the poor and needy. Ṣadaqah not only benefits the recipients, but also offers spiritual rewards to the giver from Allah (SWT). Just as zakāh (obligatory almsgiving), ṣadaqah strengthens social bonds and reduces economic disparities. In Northern Nigeria, the practice of ṣadaqah has been intertwined with the phenomenon of commercial begging, particularly among young students of Islam (Almajirai). This study critically examines the misassociation of commercial street begging with ṣadaqah, presenting an authentic Islamic perspective to promote genuine philanthropy among Muslims. Utilising qualitative research methodology, the study analyses data to highlight the potential of waqf (religious endowments) and zakāh as sustainable solutions to societal needs. It advocates for empowering the youth through education, entrepreneurship, and vocational training to reduce begging and foster peace and prosperity in the region. By addressing these issues, this paper aims to bridge the gap between religious teachings and contemporary challenges, offering practical solutions rooted in Islamic principles.